The Influence of Career Development and Work Environment on Employee Performance Mediated by Work Motivation - Sari, Narolytha Lenny; Kasmir, Kasmir (Universitas Mercu Buana, 2025)
This study aims to describe the influence of career development and work environment on employee performance, with work motivation as an intervening variable in the Marketing Directorate of PT Asuransi RIB. The study was conducted in the Marketing Directorate of PT Asuransi RIB, involving 120 respondents as the research sample. The sampling technique used was non-probability sampling with the incidental sampling method.Data analysis was performed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with the assistance of SmartPLS 3.2.9 software. The Partial Least Square (PLS) model evaluation consisted of outer model and inner model assessments, along with hypothesis testing.The results of the analysis indicate the following:Career development does not have a significant effect on employee performance,work environment does not have a significant effect on employee performance,career development has a positive and significant effect on work motivation,Work environment has a positive and significant effect on work motivation,Work motivation has a positive and significant effect on employee performance,Career development positively affects employee performance through work motivation as an intervening variable.Work environment positively affects employee performance through work motivation as an intervening variable.The findings suggest that although career development and work environment do not directly impact employee performance, they enhance work motivation, which ultimately leads to improved employee performance.